Validation of the SenseWear armband in circuit resistance training with different loads - Benito, P. J.; Neiva, C. [UNESP]; Gonzalez-Quijano, P. S.; Cupeiro, R.; Morencos, E.; Peinado, A. B. (Springer, 2012)
The use of the SenseWear (TM) armband (SWA), an objective monitor of physical activity, is a relatively new device used by researchers to measure energy expenditure. These monitors are practical, relatively inexpensive and easy-to-use. The aim of the present study was to assess the validity of SWAs for the measurement of energy expenditure (EE) in circuit resistance training (CRT) at three different intensities in moderately active, healthy subjects. The study subjects (17 females, 12 males) undertook CRT at 30, 50 and 70% of the 15 repetition maximum for each exercise component wearing an SWA as well as an Oxycon Mobile (OM) portable metabolic system (a gold standard method for measuring EE). The EE rose as exercise intensity increased, but was underestimated by the SWAs. For women, Bland-Altman plots showed a bias of 1.13 +/- A 1.48 METs and 32.1 +/- A 34.0 kcal in favour of the OM system, while for men values of 2.33 +/- A 1.82 METs and 75.8 +/- A 50.8 kcal were recorded.
Keywords: Physical activity assessment; Energy expenditure; Accelerometer; Resistance training